The behaviour of alumina reinforce metal matrix composite with nanosized particle addition / Jamaliah Md Said - Md Said, Jamaliah (2011)
Development of lightweight metal matrix composites (MMCs) has been studied with different weight composition of reinforcement materials. Alumina (AI2O3) in micron and nanosized powders were used to develop high strength and light-weight aluminum matrix composites material. The samples were produced via powder metallurgy (PM) method. The powder mixtures were ball milled before uniaxially pressed and sintered in nitrogen gas environment. This research was done to develop a powder metallurgy (PM) processes that enable the dispersion of nanosized powders. The dispersion technique was added in powder metallurgy (PM) process to disperse the micron and nano- AI2O3 powders. The effect of alumina (AI2O3) content and size on the mechanical properties of the composites was also investigated. The relationship between morphological characteristics and mechanical properties of new developed material was examined. The results showed that the homogeneous distribution of powders mixture had improved the mechanical properties with the addition of micro and nano-AbOs. The optimum for hardness is 53.32 HV, strength of 74.66 MPa as well as toughness of 25 kJ/m2 in composition containing 90 wt% pure aluminum + 7.5 wt% alumina (AkCbXum) + 2.5 wt% alumina (AfeOaXnm). However, the mechanical properties of the composite became poor when the composition of nanoAI2O3 is more than 7.5 wt%. From the morphological study showed that the nanosized alumina (AI2O3) powders tend to agglomerate with the increasing of nano- AI2O3 powders. The potential application for this new developed composite material is likely to be in automotive and aircraft industries where improvement in hardness, density, and strength as well as toughness is demanded.